Effects of Internet Popular Opinion Leaders (iPOL) Among Internet-Using Men Who Have Sex With Men - Ko, Nai-Ying; Hsieh, Chao-Hsien; Wang, Ming-Chi; Lee, Chiang; Chen, Chun-Lin; Chung, An-Chun; Hsu, Su-Ting (JMIR Publications, 2013)
BackgroundThe Internet has become a popular venue for facilitating sex networking for men who have sex with men (MSM). ObjectiveThe study aimed to evaluate the effectiveness of Internet popular opinion leaders (iPOL) in disseminating information about the human immunodeficiency virus (HIV), increasing the frequency of HIV testing, and reducing risky behaviors among MSM in Taiwan. MethodsA quasi-experimental study with a nonequivalent control website for comparison was used to estimate the effectiveness of iPOL. A community-level intervention, iPOL, was conducted at the Facebook social networking website and at top1069 as a control. The iPOLs actively disseminated HIV-related information via the platform of Internet opinion leaders and AIDS information center, and discussed and responded to questions or replied to Internet-using MSM. ResultsA total of 369 iPOLs posted 432 articles and 503 replies to others, influencing 959,088 persons on Facebook. A total of 1037 MSM, 552 (53.23%) from an intervention website and 485 (46.76%) from a control website, participated in the follow-up study survey (response rate 96%). At the 6-month follow-up after the intervention was conducted, MSM who visited the intervention website were more likely to receive HIV-related information (25.49% versus 10.47%, P<.001), discuss HIV issues with others (41.88% versus 23.79%, P<.001), review articles about HIV (90.58% versus 79.73%, P<.001), and be asked about or discuss HIV-related questions (51.11% versus 31.78%, P<.001) than those on the control website. In addition, MSM were more likely to have HIV tests within 6 months (43.89% versus 22.31%, P<.001) and consistently use condoms during anal sex with online sex partners than those using the control website (34.15% versus 26.19%, P=.004). ConclusionsThe study showed the feasibility and effectiveness of the iPOL intervention as an online HIV prevention program. These findings underscore the importance of disseminating HIV information online, as well as the challenges inherent in the efforts of iPOL to reduce HIV-related risky behaviors among Internet-using MSM.